Effect of Natural Feeding Capacity of Dengue Mosquito (Aedes aegypti) Larvae and Different Stocking Densities of Gold Molly Panda Fish (Poecilia spp) on the Feeding Speed and Function of Natural Predators in Gold Molly Panda Fish (Poecilia spp) - Anastasia Sri Endang Purwatiningsih; Mateus Salvador; Julvira Grasseli Nunnes; Joao Dos Santos; Teonori da Costa Martins (Universitas Katolik Indonesia Atma Jaya, 2023)
The Gold Molly Panda (Poecilia Spp) freshwater ornamental fish is a type of fish that is easy to care for, and bred with high tolerance for the water and environment, lots of diversity, and has good economic value in the ornamental fish market. This interdisciplinary research was aimed at observing the consumption rate and number of natural feedings of dengue mosquito (Aedes aegypti) larvae by Gold Molly Panda (Poecilia Spp) fish with different stocking densities in quantitative apprach in ANOVA two factors whit 10 times replication design using 3 differences in the density of fish stocking groups Gold Panda Molly fish (Poecilia Spp) fish as natural predator and another side to combated or eradication of dengue mosquito (Aedes aegypti) in larvae stages. The scholar has proven that the factors number of feeding and has a very significant effect on the speed of consumption of Gold Molly Panda (Poecilia Spp) fish. The results of the comparison analysis have provided recommendations for application that the stocking density of Gold Molly Panda (Poecilia Spp) fish 2 – 4 tails can be eaten between 25 – 75 larvae of the dengue mosquito (Aedes aegypti) in an average time of 133 - 186.67 minutes.